2005
DOI: 10.4049/jimmunol.174.8.4870
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of β-Defensin Expression in Human Skin by Microbial Stimuli

Abstract: In response to infection, epithelia mount an innate immune response that includes the production of antimicrobial peptides. However, the pathways that connect infection and inflammation with the induction of antimicrobial peptides in epithelia are not understood. We analyzed the molecular links between infection and the expression of three antimicrobial peptides of the β-defensin family, human β-defensin (hBD)-1, hBD-2, and hBD-3 in the human epidermis. After exposure to microbe-derived molecules, both monocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
184
0
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(206 citation statements)
references
References 36 publications
13
184
0
7
Order By: Relevance
“…In addition to several cytokines, the present studies indicated that the hBD-2 and NGAL genes are targets for IκB-ζ -mediated transcription. Consistent with the induction spectrum of IκB-ζ , both the hBD-2 and NGAL genes are induced preferentially by IL-1β, but not by TNF-α in A549 human lung adenocarcinoma cells, keratinocytes and other cells [25][26][27][28][29][30]. A recent report has also shown critical roles for IκB-ζ in IL-1β-dependent induction of the genes [38].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In addition to several cytokines, the present studies indicated that the hBD-2 and NGAL genes are targets for IκB-ζ -mediated transcription. Consistent with the induction spectrum of IκB-ζ , both the hBD-2 and NGAL genes are induced preferentially by IL-1β, but not by TNF-α in A549 human lung adenocarcinoma cells, keratinocytes and other cells [25][26][27][28][29][30]. A recent report has also shown critical roles for IκB-ζ in IL-1β-dependent induction of the genes [38].…”
Section: Discussionsupporting
confidence: 50%
“…In the present study, we analysed the molecular mechanisms of the IκB-ζ -mediated transcriptional activation. We focused on hBD-2 (human β-defensin 2) and NGAL (neutrophil gelatinase-associated lipocalin), both of which are preferentially induced by stimulators of TLR/IL-1 receptor signalling pathways, rather than by TNF-α [25][26][27][28][29][30]. We found that the promoters of both genes are synergistically activated by co-transfection of IκB-ζ and NF-κB.…”
Section: Introductionmentioning
confidence: 99%
“…The alterations in α-defensin have since been considered to be associated with the etiology of various intestinal disorders such as cystic fibrosis [4] and Crohn's disease (CD) [5]. Conversely, β-defensin (HBD) is produced by the epithelial cells particularly in the bronchus and colon, which includes 6 isotypes, HBD1 -6 [6][7][8][9][10]. While HBD1 is constitutively expressed, HBD2 and 3 are inducible defensins.…”
Section: Introductionmentioning
confidence: 99%
“…Like α-defensins, hBDs have three disulphide moieties of cysteine linking residues 1-5, 2-4, and 3-6. hBD1 was first identified in haemodialysate fluid [70] and then from urogenital tissues, skin, intestine, and other tissues [61][62][63][64][65][66][67][68][69]71]. In vitro experiments show that hBD1 is constitutively expressed and that its production is not influenced by bacterial exposure, while other hBDs are inducible when exposed to bacteria [67,[72][73][74][75]. In particular, hBD2, first identified from skin [8], is highly responsive to bacteria, pro-inflammatory stimuli (IL−1β, TNFα, LPS), and phorbol myristate acetate [63,72,74,[76][77][78][79].…”
Section: Defensinsmentioning
confidence: 99%